Gate-voltage-modulated electrostatic interaction between the probe and the channel material of FET biosensors for detecting telomerase. Issue 35 (5th April 2023) - Zhang, Hongyuan; Zheng, Zhi; Zhang, Zhicheng; Hai, Liang; Li, Haiyang; Liu, Shenghong; Lou, Xiaoding; Zhai, Tianyou; Xia, Fan
Abstract : A novel gate-voltage-modulated strategy based on FET biosensors is developed to comprehensively improve the detection performance of telomerase. Abstract : A gate-voltage-modulated strategy was proposed to improve the detection performance of telomerase. We comprehensively investigated the mechanism for the gate-voltage-modulated detection performance by modulating the electrostatic interaction between charges of a single-stranded DNA probe and electrons of the In2 O3 channel. This gate-voltage-modulated interaction between the probe and the channel can potentially serve as a universal strategy for high-performance FET biosensors.